Muhammadiyah’s Fatwa about Hewan Kurban in 2005: A Study on Muhammadiyah’s Method in Producing Fatwa - Muhammad Hilali Basya (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2019)
The Majelis Tarjih of Muhammadiyah had issued a fatwa about hewan kurban (slaughtered animal for ‛Id al-Adha) in 2005. The fatwa asked Muslims to prioritize their money to support and aid sufferers of natural disaster in in Aceh and other places. The fatwa is controversial, because it produces new form of ‛Idul Adha. This article aims to explore the method used by the Majelis Tarjih in issuing the fatwa.